2016
DOI: 10.1093/mnras/stw2542
|View full text |Cite
|
Sign up to set email alerts
|

The life cycles of Be viscous decretion discs: time-dependent modelling of infrared continuum observations

Abstract: We apply the viscous decretion disc (VDD) model to interpret the infrared disc continuum emission of 80 Be stars observed in different epochs. In this way, we determined 169 specific disc structures, namely their density scale, ρ 0 , and exponent, n. We found that the n values range mainly between 1.5 and 3.5, and ρ 0 varies between 10 −12 and 10 −10 g cm −3 , with a peak close to the lower value. Our large sample also allowed us to firmly establish that the discs around early-type stars are denser than in lat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
104
4
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(156 citation statements)
references
References 48 publications
31
104
4
17
Order By: Relevance
“…Because the emission is weak and the Balmer decrement too steep, the disks found by X-shooter are too tenuous to allow a reliable measurement of the Balmer decrement. This is in agreement with A108, page 7 of 43 A&A 609, A108 (2018) Vieira et al (2017), who found that disks of late-type Be stars are less dense than those of early-type stars. As mentioned above, there is also a general agreement that late-type Be stars show less variability than early-type stars.…”
Section: Disk Properties As a Function Of Spectral Typesupporting
confidence: 88%
“…Because the emission is weak and the Balmer decrement too steep, the disks found by X-shooter are too tenuous to allow a reliable measurement of the Balmer decrement. This is in agreement with A108, page 7 of 43 A&A 609, A108 (2018) Vieira et al (2017), who found that disks of late-type Be stars are less dense than those of early-type stars. As mentioned above, there is also a general agreement that late-type Be stars show less variability than early-type stars.…”
Section: Disk Properties As a Function Of Spectral Typesupporting
confidence: 88%
“…(2010) and Vieira et al (2017). Our best-fitting combined model from Hα spectroscopy, Hα interferometry and SED fitting has a power law density fall off, n, of 2.3 and an initial density at the stellar surface of ρ 0 = 1.0 × 10 −11 g · cm −3 with a inclination constrained by Hα spectroscopy and interferometry of 45 • ± 5 • .…”
Section: Introductionmentioning
confidence: 78%
“…Vieira et al (2015) studied the continuum emission of this system using pseudo-photosphere model and obtained n of 2.5 and log ρ 0 of ∼ −11.48. Most recently, Vieira et al (2017) used IRAS, Japanese Aerospace infrared satellite (AKARI) and Wide-field Infrared Survey Explorer (WISE) observations to constrain their viscous decretion disk model. Vieira et al (2017) find n of 2.9, 2.8 and 2.7 and log ρ 0 of -11.4, -11.4 and -11.5, using IRAS, AKARI and WISE data, respectively.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations